The Influence Of Celebrity Endorsement And Price On Purchase Intention Mediated By Brand Awareness On Kahf Products - Robita, Naufal Dzaki; Hendri , M. Irfani; Fitriana , Ana; Listiana , Erna; Ahmadi, Ahmadi (CV. Utami, 2025)
This study aims to analyze the influence of Celebrity Endorsement, Price, and Brand Awareness on Purchase Intention of Kahf products among the residents of Pontianak City. The research employs a quantitative method with a causal associative approach, and data were collected through an online questionnaire using a Likert scale, distributed to 204 purposively selected respondents. The analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The results indicate that Brand Awareness, Price, and Celebrity Endorsement have a significant effect on Purchase Intention, both directly and indirectly. Brand Awareness also acts as a mediator in the relationship between Price and Celebrity Endorsement and consumers’ Purchase Intention. These findings highlight the importance of brand strength, celebrity-based promotional strategies, and appropriate pricing in enhancing consumer interest in local products such as Kahf.